1996
DOI: 10.1093/ndt/11.supp9.18
|View full text |Cite
|
Sign up to set email alerts
|

Successful immunosenescence and the remodelling of immune responses with ageing

Abstract: In recent decades, major theoretical and technological advances have been achieved in the field of immunology. These have allowed the scientific community to analyse the immune system in a much more sophisticated manner than was possible even 20 years ago. Moreover, great theoretical changes have also occurred in gerontology-in particular, the hypothesis has been put forward that ageing and diseases are two different phenomena, and that successful ageing, i.e. ageing in good psychophysical conditions, is reall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 76 publications
0
35
0
3
Order By: Relevance
“…This regulation of peripheral T cell pool by thymic migrants is strongly supported by the findings on centenarians that show a relatively normal number of naive and memory T cells, together with a functional T cell repertoire [85]. However, it is still not clear how thymic export is regulated as to date no firm feedback loops have been defined between events in the peripheral T cell pool feeding back on the thymus to increase thymic output [86].…”
Section: Continuous Thymic Export Throughout Lifementioning
confidence: 78%
“…This regulation of peripheral T cell pool by thymic migrants is strongly supported by the findings on centenarians that show a relatively normal number of naive and memory T cells, together with a functional T cell repertoire [85]. However, it is still not clear how thymic export is regulated as to date no firm feedback loops have been defined between events in the peripheral T cell pool feeding back on the thymus to increase thymic output [86].…”
Section: Continuous Thymic Export Throughout Lifementioning
confidence: 78%
“…Only a small reduction in T lymphocytes with age and a relatively normal number of naive and memory T cells together with a functional T cell repertoire has been reported [35]. Moreover, the thymus has been shown to play a determining role in the establishment of longterm cytolytic T cell memory [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in humans have demonstrated an increase in overall numbers of circulating NK cells, with little or no loss in cytolytic activity, either toward sensitive tumor targets or when non-MHC restricted activity was assessed (105,106). A detailed phenotypic analysis of peripheral blood mononuclear cell (PBMC) demonstrated little or no age-related alteration in NK cell activity in healthy subjects recruited per strict SENIEUR protocol adherence (206).…”
Section: Natural Killer and Natural Killer T Cellsmentioning
confidence: 99%